2016
DOI: 10.1039/c6tb01647b
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of graphene-based materials

Abstract: Current efforts in the formulation of graphene-based nanocomposites with antimicrobial and antibiofilm activities in fighting against bacterial targets are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
145
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 275 publications
(147 citation statements)
references
References 178 publications
(190 reference statements)
2
145
0
Order By: Relevance
“…Graphene, composed of a single layer of carbon atoms arranged in a hexagonal lattice, is the superstar of the 2D material family, and GMs are the most explored 2D materials for antimicrobial applications . Their sharp edges, enormous basal planes, and surface moieties endow GMs with intrinsic antimicrobial activity mainly through physical interactions with microorganisms and/or by inducing oxidative stress.…”
Section: Antimicrobial Activity Of Gmsmentioning
confidence: 99%
“…Graphene, composed of a single layer of carbon atoms arranged in a hexagonal lattice, is the superstar of the 2D material family, and GMs are the most explored 2D materials for antimicrobial applications . Their sharp edges, enormous basal planes, and surface moieties endow GMs with intrinsic antimicrobial activity mainly through physical interactions with microorganisms and/or by inducing oxidative stress.…”
Section: Antimicrobial Activity Of Gmsmentioning
confidence: 99%
“…[21][22][23] For instance, graphene (and graphene oxide) has been systematically studied 24 for its antimicrobial activities, [25][26][27][28] along with its underlying molecular mechanisms. [29][30][31][32] It was revealed that graphene and graphene oxide nanosheets can cut into cell membranes, 32 extract large amount of phospholipids, 32 and create holes (pores) on cell membranes, 33 through large scale molecular dynamics simulations.…”
mentioning
confidence: 99%
“…First, AgNPs may accumulate in the tissues, and Ag ions (Ag + ) may cause local or systemic side effects at high dosages or prolonged use, including allergic reactions, skin staining, and cellular toxicity. [16][17][18] Therefore, although it is not confirmed by experimental evidence to our knowledge, the manifestation of nanocarbon's antimicrobial activity in a multimodal manner might give them an edge in escaping from or delaying the development of microbial resistance. [14,15] Antimicrobial nanocarbons such as single-walled carbon nanotubes (SWCNTs), multiwalled carbon nanotubes (MWCNTs), and graphene materials (GMs), on the contrary, seemingly function through the damaging of cellular envelopes via the combinational effect of multiple "physicochemical" routes.…”
Section: Introductionmentioning
confidence: 86%
“…For instance, depending on the degree of oxidation, the C/O ratio of the products from the Hummers method might typically be as low as ≈2-4, which correspond to 20-35% of O. [17,143,157] Nanodots and Nanodiamonds [49,51] Besides, not only the overall C/O ratios but also the abundance profiles of O-containing functional groups, such as carboxyl, carbonyl, hydroxyl, and epoxy groups, change as a result of the production and post-synthesis treatments.…”
Section: Structure-property Relationshipsmentioning
confidence: 99%